PD-L1, TIM-3, and CTLA-4 Blockade Fails To Promote Resistance to Secondary Infection with Virulent Strains of Toxoplasma gondii - Splitt, Samantha D. (Infect Immun, 2018)
T cell exhaustion is a state of hyporesponsiveness that develops during many chronic infections and cancer. Neutralization of inhibitory receptors, or “checkpoint blockade,” can reverse T cell exhaustion and lead to beneficial prognoses in experimental and clinical settings. Whether checkpoint blockade can resolve lethal acute infections is less understood but may be beneficial in vaccination protocols that fail to elicit sterilizing immunity. Since a fully protective vaccine for any human parasite has yet to be developed, we explored the efficacy of checkpoint inhibitors in a mouse model of Toxoplasma gondii reinfection. Mice chronically infected with an avirulent type III strain survive reinfection with the type I RH strain but not the MAS, GUY-DOS, and GT1 parasite strains. We report here that mouse susceptibility to secondary infection correlates with the initial parasite burden and that protection against the RH strain is dependent on CD8 but not CD4 T cells in this model. When given a lethal secondary infection, CD8 and CD4 T cells upregulate several coinhibitory receptors, including PD-1, TIM-3, 4-1bb, and CTLA-4. Moreover, the gamma interferon (IFN-γ) response of CD8 but not CD4 T cells is significantly reduced during secondary infection with virulent strains, suggesting that checkpoint blockade may reduce disease severity. However, single and combination therapies targeting TIM-3, CTLA-4, and/or PD-L1 failed to reverse susceptibility to secondary infection. These results suggest that additional host responses, which are refractory to checkpoint blockade, are likely required for immunity to this pathogen.